2012
DOI: 10.1002/jtr.1869
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Granger Causality and the Dynamics Relationship Between Real Tourism Receipts, Real Income and Real Exchange Rates in Malaysia

Abstract: This study applies the bounds testing approach, error‐correction modelling and persistence profile to analyse the dynamic relationship between real tourism receipts, real income and real exchange rates in Malaysia. The present study covers the annual sample period from 1974 to 2009. The results reveal that a long‐run relationship exists between the variables. In the short run, this study finds no Granger causality between real tourism receipts and real income, whereas there is bidirectional causality in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 37 publications
(55 reference statements)
3
61
0
Order By: Relevance
“…Before starting the bounds test, it was important to find out the orders of integration for each variable by employing an augmented Dickey-Fuller (ADF) test and Phillips and Perron (PP) test [10,11,12]. The ADF and PP tests have been employed to identify the orders of integration of each variable.…”
Section: Data Methodology and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before starting the bounds test, it was important to find out the orders of integration for each variable by employing an augmented Dickey-Fuller (ADF) test and Phillips and Perron (PP) test [10,11,12]. The ADF and PP tests have been employed to identify the orders of integration of each variable.…”
Section: Data Methodology and Resultsmentioning
confidence: 99%
“…On the other hand, Tang [12] found a long-run relationship from real income and real exchange rates to Malaysian real tourism receipts; long-run relationship from real tourism receipts and real exchange rates to Malaysian real income; short-run relationship from real exchange rates to Malaysian real income and real tourism receipts. Tang [12] also highlighted that the exchange rates is an important factor for international tourists to decide their destination for tourism.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Lau et al (2009) found evidence of uni-directional causality running from tourism to economic growth, while Tang (2011) suggested the opposite direction of causality. Moreover, Lean and Tang (2010) and Tang (2013a) endorsed the view that tourism and economic growth in Malaysia have bidirectional causality, particularly in the long-run. Furthermore, Lean and Tang (2010) used the rolling causality approach to confirm the results, and they found that tourism is a potential source of economic growth in Malaysia.…”
Section: Insights From the Literaturementioning
confidence: 99%
“…They used the Granger causality test in a bi-variate framework to verify the direction of causality between tourism and economic growth in Lebanon. Lütkepohl (1982) and Tang (2013a), however, have documented that Granger causality tests in a bi-variate framework are likely to produce biased results owing to the omission of relevant variables. Apart from this imperfection, we find that none of the studies, especially for Lebanon, has examined the stability of the tourism-led growth hypothesis, which is important for policymakers to identify the actual engine of growth for Lebanon.…”
Section: Introductionmentioning
confidence: 99%